Strategi Pemasaran dalam Bentuk Promosi Terhadap Minat Beli Konsumen Studi Deskriptif : CGV Cinemas – Central Park - Lusia Debora; Eko Harry Susanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
A company have a different marketing strategy. The purpose of this research carried out with the title "Marketing Strategy in the Form of Promotion of Consumer Purchasing Interests is to find out the marketing strategy carried out by CGV Cinemas and find out which promotion elements are more in demand by CGV Cinemas consumers located in Central Park Mall. This research was conducted by using descriptive qualitative methods, the technique of collecting primary data was done by means of interviews and secondary data collection techniques through books that were relevant to the object of research, the internet and the annual report of CGV Cinemas. The results of this study indicate that CGV Cinemas consumers know the marketing strategy in the form of CGV Cinemas promotion through advertising media, publications, direct sales, sales promotions and face-to-face sales that encourage consumers to make purchases.